PENERAPAN PSAK 65 DALAM HUBUNGAN PUSAT DAN CABANG TOKO BANGUNAN USAHA BARU - Ramadhani, Ilas; Huda, Naimatul; Amanda, Putri; Putra, Yosep Eka; ., Megarahmi (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2025)
This research is motivated by the weak implementation of accounting in MSMEs that have developed into more than one business unit, such as Toko Bangunan Usaha Baru, which, despite having a head office and branches, does not implement a structured financial recording and reporting system. This study aims to determine the current state of financial recording, identify the factors causing the lack of an adequate accounting system, and provide recommendations for implementing standardized head office and branch accounting to produce reliable financial information. The study used a qualitative approach with interviews and direct observation methods with the business owner as the primary data source. The results showed that the business does not have financial records, does not determine asset depreciation, does not separate private transactions, does not record central-branch inventory movements, and does not have financial reports. Recommendations provided include the implementation of daily cash books, stock cards, recording central-branch asset movements, determining owner salaries, calculating fixed asset depreciation, and preparing basic financial reports in accordance with PSAK EMKM. These findings confirm that the implementation of an appropriate accounting system can improve the accuracy of financial information and become the basis for more effective business decision-making.